Electrocatalytic water oxidation by CuII complexes with branched peptides. Issue 29 (11th March 2015) - Pap, József S.; Szyrwiel, Łukasz; Srankó, Dávid; Kerner, Zsolt; Setner, Bartosz; Szewczuk, Zbigniew; Malinka, Wiesław
Abstract : Two Cu II complexes with branched tetrapeptides undergo PCET and catalyse water oxidation, processes promoted by the presence of C-terminal histidine. Abstract : Two mononuclear Cu II complexes with tetrapeptides incorporating al -2, 3-diaminopropionic acid (dap) branching unit are reported to undergo PCET and catalyse water oxidation. C-terminal His extension of dap (L = 2GH) instead of Gly (L = 3G) lowers the p K a for Cu III H−2 L (9.36 vs. 9.98) and improves the TOF at pH 11 (53 vs. 24 s −1 ).